Upaya Menumbuhkan Jiwa Kepemimpinan yang Kreatif dan Inovatif pada Diri Orang Muda Katolik - Evimawati Harefa; Sergius Lay; Mei Trisnawati Harefa (Jurnal Magistra, 2023)
This writing departs from the author's concern for the reality that often occurs in the leadership of Catholic Youth in fostering a spirit of leadership, where the leadership spirit of OMK is still lacking because they often forget responsibility, which is caused by the influence of the times which makes them more happy themselves, have their own opinion , act alone and boast about themselves, so that they still have not found their true identity as OMK. The purpose of this writing is to understand and understand the theory of OMK leadership and to understand the spirit of creative and innovative leadership in OMK. The method used in this thesis is literature review. Thus, from the theory that has been described, it is hoped that OMK will be able to carry out their responsibilities in realizing the ideals and hopes of the Church, because OMK are individuals who still have a fresh leadership spirit and are still strong in service. Through OMK the Church will be assisted in various services both liturgically, ministry and pastoral. Therefore, if OMK is to be a true leader, they must be able to challenge a process, be able to work together, give themselves, be humble, and be able to apply good moral values ​​to everyone.